Evolution and Functional Divergence of SUN Genes in Plants - Yuan, Li; Pan, Jingwen; Zhu, Shouhong; Li, Yan; Yao, Jinbo; Li, Qiulin; Fang, Shengtao; Liu, Chunyan; Wang, Xinyu; Li, Bei; Chen, Wei; Zhang, Yongshan (Frontiers in Plant Science, 2021)
SUN-domain containing proteins are crucial nuclear membrane proteins involved in a plethora of biological functions, including meiosis, nuclear morphology, and embryonic development, but their evolutionary history and functional divergence are obscure. In all, 216 SUN proteins from protists, fungi, and plants were divided into two monophyletic clades (Cter-SUN and Mid-SUN). We performed comprehensive evolutionary analyses, investigating the characteristics of different subfamilies in plants. Mid-SUNs further evolved into two subgroups, SUN3 and SUN5, before the emergence of the ancestor of angiosperms, while Cter-SUNs retained one subfamily of SUN1. The two clades were distinct from each other in the conserved residues of the SUN domain, the TM motif, and exon/intron structures. The gene losses occurred with equal frequency between these two clades, but duplication events of Mid-SUNs were more frequent. In cotton, SUN3 proteins are primarily expressed in petals and stamens and are moderately expressed in other tissues, whereas SUN5 proteins are specifically expressed in mature pollen. Virus-induced knock-down and the CRISPR/Cas9-mediated knockout of GbSUN5 both showed higher ratios of aborted seeds, although pollen viability remained normal. Our results indicated divergence of biological function between SUN3 and SUN5, and that SUN5 plays an important role in reproductive development.